2002
DOI: 10.1016/s0893-133x(01)00332-3
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Fos Expression in the CA3 Region of the Hippocampus in Spatial Memory Formation in Rats

Abstract: Activity-dependent plastic changes in the strength

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 35 publications
(55 reference statements)
5
98
0
Order By: Relevance
“…Because the molecules that were reduced in the dentate gyrus of FYN/hAPP low mice are critically involved in the formation or consolidation of memories (Molinari et al, 1996;Atkins et al, 1998;Blum et al, 1999;Guzowski et al, 2000;Guzowski, 2002;He et al, 2002), we next assessed the spatial learning and memory of mice in the Morris water maze. NTG, hAPP low , FYN, and FYN/hAPP low mice were able to learn both the cued (platform location visible) and the spatial (platform hidden) components of this task (Fig.…”
Section: Cooperation Of Fyn and Happ/a␤ Impairs Spatial Memory Retentmentioning
confidence: 99%
“…Because the molecules that were reduced in the dentate gyrus of FYN/hAPP low mice are critically involved in the formation or consolidation of memories (Molinari et al, 1996;Atkins et al, 1998;Blum et al, 1999;Guzowski et al, 2000;Guzowski, 2002;He et al, 2002), we next assessed the spatial learning and memory of mice in the Morris water maze. NTG, hAPP low , FYN, and FYN/hAPP low mice were able to learn both the cued (platform location visible) and the spatial (platform hidden) components of this task (Fig.…”
Section: Cooperation Of Fyn and Happ/a␤ Impairs Spatial Memory Retentmentioning
confidence: 99%
“…The training procedure was as described previously. 4,8 Before the actual training began, the animals were shaped for 4 days to run to end of the arms and consume the bait, in groups of four. The bait was initially available throughout the maze, but gradually was restricted to the food cup.…”
Section: Radial Arm Maze Taskmentioning
confidence: 99%
“…[5][6][7] To examine whether spatial learning and memory are associated with activation of BDNF/TrkB signaling, phosphorylated TrkB was measured in the hippocampus of rats trained for the spatial reference and working memory task in a radial arm maze. 4,8 Figure 1a shows the changes in performance produced by daily training (three trials per day). An ANOVA with repeated measures revealed a significant effect of training on reference (F(7,84) ¼ 60.890, Po0.0001) and working memory (F(7,84) ¼ 40.209, Po0.0001), indicating spatial memory formation.…”
mentioning
confidence: 99%
“…However, the functional significance of the up-regulation of c-fos gene expression and Fos protein synthesis in these brain sites remains unclear. Several studies have shown that reversible blockage of Fos protein production by the application of a specific antisense oligodeoxynucleotide (AS-ODN) against c-fos mRNA (c-fos AS-ODN) in the brain is useful for studying the function of the c-fos gene and Fos protein (7,(24)(25)(26). Here, we studied the potential roles of Fos protein in the PBN, AMY, and IC in CTA formation using the AS-ODN-mediated disruption of Fos production in vivo.…”
mentioning
confidence: 99%